A facile corrosion approach to the synthesis of highly active CoOx water oxidation catalysts. Issue 10 (22nd February 2017) - Indra, Arindam; Menezes, Prashanth W.; Das, Chittaranjan; Göbel, Caren; Tallarida, Massimo; Schmeiβer, Dieter; Driess, Matthias
Abstract : Room temperature partial oxidation (corrosion) of cubic CoO led to the formation of mixed valence CoO x with better electrochemical water oxidation activities in alkaline pH. Activation of both octahedral Co 3+ and Co 2+ to layered oxohydroxide–hydroxide during alkaline electrochemical water oxidation has been demonstrated. Abstract : Ultra-small rock salt cobalt monoxide (CoO) nanoparticles were synthesized and subjected to partial oxidation ('corrosion') with ceric ammonium nitrate (CAN) to form mixed-valence CoO x (1 < x < 2) water oxidation catalysts. Spectroscopic, microscopic and analytical methods evidenced a structural reformation of cubic CoO to active CoO x with a spinel structure. The superior water oxidation activity of CoO x has been established in electrochemical water oxidation under alkaline conditions. Electrochemical water oxidation with CoO x was recorded at a considerably low overpotential of merely 325 mV at a current density of 10 mA cm −2 in comparison to 370 mV for CoO. Transformation of both octahedral Co II and Co III sites into amorphous Co(OH)2 –CoOOH is the key to high electrochemical activity while the presence of a higher amount of octahedral Co III sites in CoO x is imperative for an efficient oxygen evolution process.